Gelsolin amyloid angiopathy causes severe disruption of the arterial wall. Issue 8 (20th May 2016) - Koskelainen, Susanna; Pihlamaa, Tiia; Suominen, Sinikka; Zhao, Fang; Salo, Tuula; Risteli, Juha; Baumann, Marc; Kalimo, Hannu; Kiuru‐Enari, Sari
Abstract : Hereditary gelsolin amyloidosis (HGA) is a dominantly inherited systemic disease reported worldwide. HGA is characterized by ophthalmological, neurological, and dermatological manifestations. AGel amyloid accumulates at basal lamina of epithelial and muscle cells, thus amyloid angiopathy is encountered in nearly every organ. HGA patients have cardiovascular, hemorrhagic, and potentially vascularly induced neurological problems. To clarify pathomechanisms of AGel angiopathy, we performed histological, immunohistochemical, and electron microscopic analyses on facial temporal artery branches from 8 HGA patients and 13 control subjects. We demonstrate major pathological changes in arteries: disruption of the tunica media, disorganization of vascular smooth muscle cells, and accumulation of AGel fibrils in arterial walls, where they associate with the lamina elastica interna, which becomes fragmented and diminished. We also provide evidence of abnormal accumulation and localization of collagen types I and III and an increase of collagen type I degradation product in the tunica media . Vascular smooth muscle cells appear to be morphologically and semi‐quantitatively normal, only their basal lamina is often thickened. In conclusion, angiopathy in HGA results in severe disruption of arterial walls, characterized by prominent AGel deposition, collagen derangement and severe elastolysis, and it may be responsible for several, particularly hemorrhagic, disease manifestations in HGA.